Heart rate as an indicator of oxygen uptake & cardiac function during two swimming modes - Emmett, J. D.; McClung, J. A. (Medicine & Science in Sports & Exercise, 1993)
Freestyle and tethered swimming measures were taken. Heart rate was not a good discriminator of aerobic properties between the two different forms of activity. HR is not a good indicator of swimming performance in different forms of swimming (freestyle and tethered swimming).